Optimization of silver nanoparticles production using Aspergillus niger and study of antimicrobial activity - Selvakumaran, Suguna; Marimuthu, Kayathri; Poopalan, Thiruvany; Tamil Selvan, Kalaiyarasi; Khairuddin, Nozieana (J K Welfare & Pharmascope Foundation, 2021)
Silver nanoparticles have attracted high attention worldwide for their various applications. The physiochemical parameters such as temperature, media, mixing ratio affect the rate of synthesis of silver nanoparticles and their yield. Thus, optimization of these physiochemical parameters is needed to enhance the production of silver nanoparticles. In this study, silver nanoparticles were synthesized using Aspergillus niger culture supernatant. The produced silver nanoparticles were characterized using UV-visible Spectrophotometer at 200nm to 700 nm, which had a peak at 450 nm, indicates the formation of silver nanoparticles. It was found that Sabouraud Dextrose Broth(SDB)as optimum media, 40 ml of supernatant and 10 ml of silver nitrate as optimum mixing ratio and 65◦C as optimum temperature to produce silver nanoparticles. The optimized silver nanoparticles were subjected to antimicrobial activity, and itwasfoundthatitishighlyeffectivetowardsgram-negativebacteriathangram-positive bacteria where the zone of inhibition for Escherichia coli was 7±2.7mm and 5.3±2.1 mm for Staphylococcus aureus.